Selenium Attenuates Ethanol-induced Hepatocellular Injury by Regulating Ferroptosis and Apoptosis - Chen, Feng; Li, Qianhui; Xu, Xiaomin; Wang, Fei (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Ferroptosis is a newly identified type of cell death which is strongly linked to the development of several diseases. Whereas, the role of ferroptosis in the improvement of ethanol-induced hepatocytes injury by selenium has not been confirmed. Materials and Methods: In this study, an in vitro cell damage model was established using half inhibition concentration of ethanol to induce NCTC clone 1469. Cell activity, lipid peroxidation, apoptosis and the expression of markers related to ferroptosis pathway was determined. A mouse model of alcoholic liver disease (ALD) was constructed and the effectiveness of selenium and ferrostatin-1 in treating ALD in vivo was assessed by serum liver function tests, tissue staining and immunohistochemistry for ferroptosis related proteins. Results: Pretreatment with selenomethionine and ebselen significantly improved ethanol-induced reduction in hepatocyte viability, elevated GSH levels and SOD enzyme activity, reduced MDA and iron content, while improving ethanol-induced changes in apoptosis levels and ferroptosis markers GPX4, SLC7A11, and ACSL4, with the effect of Selenomethionine being more significant. In vivo results also indicated that intervention with selenium or ferroptosis inhibitors significantly improved ethanol-induced liver tissue damage, significantly reduced serum ALT and AST levels, upregulated GPX4 and SLC7A11, but reduced ACSL4 protein levels in liver tissue. Conclusion: The process of ethanol damage to hepatocytes is regulated by the ferroptosis pathway. Selenium may exert a beneficial role in ethanol-induced hepatocyte injury by antagonizing oxidative stress and regulating apoptosis and ferroptosis pathways. Cite this article as: Chen F, Li Q, Xu X, Wang F. Selenium attenuates ethanol-induced hepatocellular injury by regulating ferroptosis and apoptosis. Turk J Gastroenterol. 2024;35(10):778-786.